Chipotle - Neck, Christopher P.; Houghton, Jeffery D.; Murray, Emma L. (London : SAGE Publications Ltd, 2017)
This case looks at one company's commitment to product integrity as Chipotle is based on the idea that "food with integrity" will resonate with diners in a more personal way than a value meal ever could. They corner the market with a food conscience (not just food conscious) position that attracts consumers who seek a meal with a mission. Through the ethically sourcing of their ingredients, supporting the small and local farmer and rancher, and giving back to the communities that help them thrive, Chipotle is able to be transparent and consumers are willing to pay a premium for their quick meal. The mentality that customers value healthier food options and are willing to pay more for a conscious farm-to-table approach has established a culture that is profitable and sustainable.
Originally published in Neck, C. P., Houghton, J. D., & Murray, E. L. (2016). Chipotle. Organizational behavior: A critical-thinking approach (pp. 210 212). Thousand Oaks, CA: SAGE Publications, Inc. Print. ISBN: 9781506314402.
Includes bibliographical references and index.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Chipotle Mexican Grill, Inc; Fast food restaurants -- Case studies; Product management -- Case studies; Marketing -- Management -- Case studies